Fish Consumption Campaign to Increase Protein Intake at MAN 1 Sambas - Merdekawati, Dewi; Maryono, Maryono; Agam, Beryaldi; Yunita, Nurul Fatimah (Journal of Mestika Nusantara Satu Community Services, 2024)
This fish consumption campaign was conducted at MAN 1 Sambas School, with the aim of increasing students’ interest in consuming fish. Fish consumption is very good for the body because fish is an animal food that contains protein so it is very good for the health of the body. This activity was conducted in November 2023. The approach we adopted in this activity was to provide counseling to students. The number of respondents who participated in this campaign activity amounted to 125 people with 69 women and 56 men. This form of campaign has received approval from the school. The results of this activity are expected to have a positive impact and change consumption behavior towards fish consumption to meet daily protein needs. This activity has previously been briefed and strengthened the knowledge of the benefits of fish and protein in fish. As for other things, this activity went smoothly.